2021
DOI: 10.33258/birci.v4i1.1536
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study on Internalization of Character Values through Educational Profession Course

Abstract: This study was based on the findings during teaching and learning process at FKIP Universitas Dehasen Bengkulu (the Faculty of Educational Science and Teacher Training of Dehasen University of Bengkulu). There was a phenomenon of declining of good character value and morality. This is because of the misused of advancing technology by students that brings negative impact on the students' character and morality. This phenomenon was especially found among new students of FKIP (Faculty of Educational Science and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The incorporation of Quizizz media in multimedia learning significantly influences student interest, evident through indicators such as enjoyment in learning, active participation, sustained engagement, and attentiveness to the media content. The observable student engagement underscores the positive impact of Quizizz in enriching the learning experience, thereby affirming its efficacy in fostering greater student engagement (Mesterjon et al, 2023b). To delve deeper into its value augmentation, we conducted an analysis utilizing both Data and Hypothesis Testing methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of Quizizz media in multimedia learning significantly influences student interest, evident through indicators such as enjoyment in learning, active participation, sustained engagement, and attentiveness to the media content. The observable student engagement underscores the positive impact of Quizizz in enriching the learning experience, thereby affirming its efficacy in fostering greater student engagement (Mesterjon et al, 2023b). To delve deeper into its value augmentation, we conducted an analysis utilizing both Data and Hypothesis Testing methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…Character education is defined as a genuine effort to help someone understand, care, and act on the basis of core ethical values (Alcivar et al, 2021;Starokozhko et al, 2020). Character education is a process of providing educational guidance (values, character, morals and character) to students to become fully human (characterized in the dimensions of heart, mind, body, taste and intention), and make students know, care, and internalize values so that we humans behave (Moate, 2021;Mesterjon et al, 2021). Character education is education that instills and develops noble characters (Cathrin et al, 2021).…”
Section: B Character Educationmentioning
confidence: 99%
“…Some articles explaining value internalization in group/organization (Ahmadi et al, 2020;Harnanto, 2022;Kusumaningrum & Sulistyaningsih, 2021;Mesterjon et al, 2021;Nursyamsiah, 2014;Sultoni et al, 2018;Tambak et al, 2021). All of the articles revealed that the internalization of values is done through formal education realm from senior high school to university.…”
Section: Introductionmentioning
confidence: 99%
“…Those articles also did not explain the procedure of internalization specifically. Only Mesterjon et al (2021) and Harnanto (2022) articles did explain the internalization model through exploratory study and BMT Garuda and Bupanca Media. Meanwhile, Kusumaningrum and Sulistyaningsih (2021) article discussed more the internalization of Pancasila values in adolescents through digital literacy education program.…”
Section: Introductionmentioning
confidence: 99%